Development of real-time PCR assay for differential detection of Bordetella bronchiseptica and Bordetella parapertussis - Tizolova, Anette; Brun, Delphine; Guiso, Nicole; Guillot, Sophie (Diagnostic microbiology and infectious disease, 2014)
Bordetella parapertussis is a causative agent of whooping cough in humans, and B. bronchiseptica is causing wide variety of respiratory infections in mammals, including humans. Specific diagnostic tests are not currently available. Our first objective was to develop a real-time PCR test for the specific detection of B. bronchiseptica based on the previously described end-point PCR, targeting an intergenomic sequence of the fla gene locus, but it has not been reached. However, there is cross-reactivity between B. parapertussis and B. bronchiseptica. Therefore, the targeted region of several clinical isolates of both species was sequenced, and alignment of the sequences allowed the development of a 2-step real-time PCR assay. The first PCR assay detected the DNA of all clinical isolates of both B. bronchiseptica and B. parapertussis tested. The second PCR assay detected only the DNA of B. parapertussis clinical isolates, thereby allowing discrimination between B. parapertussis and B. bronchiseptica.
Keywords: DNA bakterií; Molecular Diagnostic Techniques; Humans; diferenciální diagnóza; diagnostické techniky molekulární; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; Bordetella bronchiseptica; Diagnosis, Differential; lidé; sekvenční analýza DNA; Bordetella Infections; DNA, Bacterial; Real-time PCR; Bordetella parapertussis; Real-Time Polymerase Chain Reaction; infekce bakteriemi rodu Bordetella; kvantitativní polymerázová řetězová reakce; Diagnosis